2009
DOI: 10.1186/1423-0127-16-78
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of armepavine against hepatic fibrosis in rats

Abstract: Activation of hepatic stellate cells (HSCs) plays a crucial role in liver fibrogenesis. armepavine (Arm, C 19 H 23 O 3 N), an active compound from Nelumbo nucifera, has been shown to exert immunosuppressive effects on T lymphocytes and on lupus nephritic mice. The aim of this study was to investigate whether Arm could exert anti-hepatic fibrogenic effects in vitro and in vivo. A cell line of rat HSCs (HSC-T6) was stimulated with tumor necrosis factor-α (TNF-α) or lipopolysaccharide (LPS) to evaluate the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 47 publications
0
30
0
1
Order By: Relevance
“…(31) who found that TNF‐α up‐regulated 15% of NF‐κB signal pathway–related genes in KF compared to their normal skin counterparts. It was also recently reported that armepavine derived from the medicinal plant, Nelumbo nucifera, suppressed NF‐κB activation and up‐regulated MT gene expression in inhibiting hepatic fibrosis (30). As silencing of the MT‐2A gene in KF did not modulate Collagen 1A and Collagen 3A gene expression, it is plausible that reduction of MT‐2A facilitates NF‐κB activation, thereby promoting survival of KF and potentiating inflammation, and indirectly enhancing keloid formation.…”
Section: Discussionmentioning
confidence: 97%
“…(31) who found that TNF‐α up‐regulated 15% of NF‐κB signal pathway–related genes in KF compared to their normal skin counterparts. It was also recently reported that armepavine derived from the medicinal plant, Nelumbo nucifera, suppressed NF‐κB activation and up‐regulated MT gene expression in inhibiting hepatic fibrosis (30). As silencing of the MT‐2A gene in KF did not modulate Collagen 1A and Collagen 3A gene expression, it is plausible that reduction of MT‐2A facilitates NF‐κB activation, thereby promoting survival of KF and potentiating inflammation, and indirectly enhancing keloid formation.…”
Section: Discussionmentioning
confidence: 97%
“…Nelumbo nucifera has been used for various medicinal purposes in oriental medicine and two compounds, (R)-roemerine and N-methylasimilobine isolated from its leaf exhibited good in vitro antimalarial activity (IC 50 = 0.2 g/mL) (Agnihotri et al, 2008). Armepavine, a compound from Nelumbo nucifera, was found to exert immunosuppressive effects on T-lymphocytes in lupus nephritic mice (Weng et al, 2009). Liensinine, negferine, and isoliensinine isolated from the leaves and embryo of Nelumbo nucifera showed potent anti-HIV activity (IC 50 : 0.8 g/mL) (Kashiwada et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The dry powder prepared from its flowers has recently been used in the treatment of Diabetes mellitus by Ayurvedic physicians. Armepavine (Arm), an active compound from N. nucifera, has been shown to exert immunosuppressive effects both in vitro and in vivo through inhibition of NF-κB activation pathways [203]. In vitro , Arm suppressed NF-κB activation and MAPK (p38, ERK1/2, and JNK) phosphorylations and in vivo , Arm attenuated the mRNA expression levels of col1α2, TGF-β1, TIMP-1, ICAM-1, iNOS, and IL-6 genes.…”
Section: Introductionmentioning
confidence: 99%